Design, synthesis, and biological evaluation of a novel series of 2-(2, 6-dioxopiperidin-3-yl)isoquinoline-1, 3(2H, 4H)-dione derivatives as cereblon modulators. (31st December 2022) - Liu, Yilin; Song, Yuming; Xu, Yingju; Jiang, Meixu; Lu, Haibin
Abstract: In the current study, we designed and synthesised a novel series of 2-(2, 6-dioxopiperidin-3-yl)isoquinoline-1, 3(2 H, 4 H )-dione derivatives as cereblon (CRBN) modulators. The results of the CCK8 assay revealed potent antiproliferative activity for the selected compound 10a against NCI-H929 (IC50 =2.25 µM) and U239 (IC50 =5.86 µM) cell lines. Compound 10a also can inhibit the TNF-α level (IC50 =0.76 µM) in LPS stimulated PMBC and showed nearly no toxicity to this normal human cell line. The TR-FRET assay showed compound 10a having potent inhibitory activity against CRBN (IC50 =4.83 µM), and the docking study confirmed a nice fitting of 10a into the active sites of CRBN. Further biology studies revealed compound 10a can increase the apoptotic events, arrest the NCI-H929 cells at G0/G1 cell cycle, and induce the ubiquitination degradation of IKZF1 and IKZF3 proteins by CRL4 CRBN . These preliminary results suggested that compound 10a could serve as a potential antitumor drug and worthy of further investigation.